Seasonal Study for Deficiency of Some Trace Elements in Sheep in Talesh Area in 2019-2020 - S Aghajani, A Hassanpour, B Amoughli-Tabrizi and A Ganjkhanloo (پژوهش های علوم دامی, 2021)
Introduction: Mineral elements required by the body of living organisms are divided into two categories: macroelements and microelements, which make up 2-5% of the body weight of animals. Minerals have vital role in the efficiency of growth, production and reproduction performances. General conditions for the deficiency of these minerals can be caused by a deficiency in food, a deficiency in the soil, or an imbalance between the amounts of minerals (Costabe et al 2017). Deficiency may be low and the appearance of the animal may not indicate anything, but all deficiencies will affect the animal sooner or later. Deficiency of some elements such as copper, selenium, zinc and magnesium is more common in areas with poor soil (Myers et al 2019). Talesh region is located in the north of Iran in the west of Gilan province and due to having large and extensive pastures in this area; it is very prosperous for sheep keeping. No complete study has been conducted on the status of rare and essential elements of livestock in this area. Therefore, this study was conducted to investigate the serum levels of some elements (magnesium, copper, zinc and selenium) and seasonal comparison in sheep in this area. Materials and methods: The study was conducted on 200 sheep in four geographical areas north, south, west and east of Talesh city (50 samples per season). In the middle of each season, after registering the livestock characteristics, serum samples were obtained at different ages under one year and one year (42 cases), two years (44 cases), three years (28 cases), four years (40 cases), five years (24 cases) and six years and above (22 cases). Sheep were in both sexes (30 cases) and females (170 cases). Sampling was done randomly. From each animal, 10 cc of blood was taken from jugular vein and the serum was separated and frozen. During the measurement, the samples were separated from the freezer and the serum values of copper, zinc and selenium were measured by atomic absorption method (model AA6300 made by SHIMADZU company of Japan) (Bye 1989) and magnesium serum was measured by Pars Azmoun biochemical kit. The results analyzed by ANOVA and Ttest to determine the difference between seasons, different groups of ages and sexes. Results and discussion: The mean serum magnesium level was higher in spring (2.81 ±0.35 mg/dl) than in other seasons and lower in winter (2.60 ± 0.35 μg/dl) than in others. The mean serum levels of copper in spring, summer, autumn and winter was 0.80 ± 0.071, 0.94 ± 0.091, 0.84 ± 0.091 and 0.60 ± 0.092 μg/dl, respectively. These means were 65.11 ±2.11, 72.10 ± 1.64, 72.00 ± 1.64 and 64.91 ± 2.36 μg/dl, respectively for zinc. The mean serum selenium levels were higher in summer (0.042 ±0.006 μg/dl) and lower in winter (0.035 ±0.005 μg/dl) than in other seasons. The differences between the seasons were significant in all elements (P < 0.05). The means of magnesium, zinc and selenium in the serum in males were higher than females nonsignificantly. The mean of serum copper was higher in the females that this increasing was not significant, also. Serum magnesium levels were higher in the 3 years than in other ages, but the difference between mean serum magnesium levels was not significant at different ages. The mean serum copper in the 5 years and the serum zinc and selenium levels in the six years were higher than in other ages, significantly (P <0.05). The high serum levels of these elements in the summer are due to the nutrition of these animals in the spring and summer from the lush and suitable forage of pastures, which will be followed by proper nutrition in the spring and the appropriate serum grade in the summer (Suttle 2010). Talesh city is located in the north of Iran and due to having suitable pastures in these two seasons, it confirms this issue. There are many species and physiological stages where the animal’s copper requirement is not known. Grazing animals can exhibit zinc deficiency when soils and forages contain limited concentrations of zinc. Pastures have been observed to be zinc-deficient in many parts of the world. However, non-ruminant animals usually receive adequate zinc when fed corn and soybean meal diets if there is not excessive calcium and iron in their diets, but this is not true for rapidly growing young animals. Characteristics of a zinc deficiency include loss of appetite, reduced growth and reproduction, and impaired health of bone and skin tissues (Myers Hill and Carlson Shannon 2019). In a study ewes supplemented with 0.300 and 0.450 mg/kg Se had increased placenta, serum, and colostrum Se levels compared with those fed the control diet (P<0.05). There was a strong positive correlation between placental and serum Se concentration in ewes (Erdogan et al 2017). In a study reported that low serum zinc levels in winter related to their pregnancy and high pneumonia occurrence in this season, in other livestock (Ramin et al 2017). Serum changes at different ages can be due to better nutrition and greater adaptability of these animals to the region. Conclusion: These results confirmed that in the cold seasons of the year, as well as at a young age, the serum levels of the magnesium, zinc, copper and selenium are low. These elements should be used parentally or additive form in the food in autumn and winter seasons in sheep in this area to prevent possible complications of their deficiency.